Analysis of the technological production of three professional master's programs in the field of nursing - Rejane Eleuterio Ferreira; Cláudia Mara de Melo Tavares
Objective: to analyze the technological production of three professional master programs in the area of Nursing. Method: documentary research on primary sources. A total of 100 graduate nurses from three professional master's programs in Nursing in the Southeastern region of Brazil were analyzed, based on the following variables: time of training, typology of products; context of products and technological and educational classification, welfare and management. The study was guided by the question: "How is the technological production of the dissertation of the professional master's degree according to typology, context and technological classification? The analysis of the data was based on the construction of a table that categorized the products according to the typology. Results: development of techniques was the main type of product found, being expressed by flowcharts, protocols, guidelines and training courses. The products were mostly developed in the hospital context, in the educational technology format. Conclusion: the technological production of the analyzed programs is restricted, diffuse and, in its majority, of low social impact and has no relevance in the body of the dissertation. Despite the wide possibility of conclusion work, the dissertation, accompanied by an article and/or technical productions, is the main form of presentation.